Monitoring system of photovoltaic panels using 433 MHz radio frequency module - Zaidan Didi; Ikram El Azami (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
In this article, we presented an innovative study that allows direct monitoring of the main parameters of photovoltaic panels. Our study focuses on the skills of radio frequency modules to send the main parameters of photovoltaic cells. In this paper, we used an Esp32 microcontroller in the radio frequency (RF) transmitter block and an Arduino Uno board in the receiver block, in addition, to measure current, we used a current sensor, and to measure voltage, we implemented a voltage divider. After that, we calculated the power and the energy. Note that the various measured and calculated values are stored and used via the ThingSpeak platform. In comparison with similar studies, our achievement presents an` effective and inexpensive solution because its operating principle is based on radio frequency transmission, so it works perfectly even in the absence of the internet. Finally, our study was very well tested without detecting any abnormalities, and the results obtained are a perfect witness to our success.